2015
DOI: 10.5056/jnm15016
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Japanese Version of the Rome III Diagnostic Questionnaire for Irritable Bowel Syndrome and Functional Dyspepsia

Abstract: Background/AimsReliable diagnostic instruments for measuring the presence of functional gastrointestinal disorders based on the Rome III criteria have been lacking in Japan. The aims of the present study were to translate and validate the Rome III diagnostic questionnaire which was widely used in Western countries. MethodsThe original version of Rome III diagnostic questionnaire was translated from English into Japanese through 3 independent forward translations, resolution, back translation and reconciliation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
(28 reference statements)
1
40
0
1
Order By: Relevance
“…We also found that the positive endoscopic and ultrasonographic findings in patients diagnosed using the questionnaire varied with the location of disease. More positive findings were observed in patients with functional esophageal and gastroduodenal disorders than in those with functional bowel disorders, which is consistent with the results of other studies . There are several possible reasons for this finding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that the positive endoscopic and ultrasonographic findings in patients diagnosed using the questionnaire varied with the location of disease. More positive findings were observed in patients with functional esophageal and gastroduodenal disorders than in those with functional bowel disorders, which is consistent with the results of other studies . There are several possible reasons for this finding.…”
Section: Discussionsupporting
confidence: 92%
“…This study suggests that the symptom‐based questionnaire is important for diagnosing FGID, especially for screening patients. Many studies have focused on validating the Rome III questionnaire, but its diagnostic accuracy varies in different populations and regions . The patients included in our study consisted of patients without red flag symptoms and those without a history of disease that could induce the GI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sex, age, and rates of H pylori infection did not differ between the patients with FD and the controls (Table ). Among the 35 patients with confirmed FD, 25 had postprandial distress syndrome and 10 had the unclassified type …”
Section: Resultsmentioning
confidence: 99%
“…18 The questionnaire was composed of 13 items regarding defecation habits and actual status. The questionnaire items are shown in the Appendix.…”
Section: Questionnaire Itemsmentioning
confidence: 99%